Contributions of a genre-based teacher education course to second language writing teachers' cognitions. Issue 2 (15th March 2023) - Nazari, Mostafa; Alizadeh Oghyanous, Parastoo
ABSTRACT: Purpose: While research on language teacher cognition is increasingly developing, the scope of research on writing teachers' cognition is still limited, particularly on how teacher education influences their cognitions. The present study moves along this line of inquiry and investigates the impact of a teacher education course on second language teachers' cognitions of argumentative writing. Design: A teacher education course was initially designed to negotiate the central issues in genre-based instruction (GBI) focusing on argumentative writing, followed by the teachers' argumentative writing instruction. Data were collected at three junctures of time before, during, and after both the teacher education course and the teachers' writing instruction, from semi-structured interviews, classroom observations, stimulated recalls, and reflective journals. Findings: The findings indicated that the teachers navigated through three lines of development: Enhanced awareness and a more professional authorial identity, enhanced pedagogical content knowledge, and developing GBI-featuring mental representations. Value: The study concludes with implications for reducing the gap between teacher education programs and teachers' subsequent writing instruction, especially helping the teachers develop and retain a professional language for representing their practice.